Aspek Hukum Dalam Etika Dan Prilaku Aparatur Sipil Negara - Muklis Muklis (Iuris Studia: Jurnal Kajian Hukum, 2022)
Basically, ethics and behavior for the State Civil Apparatus (ASN) are closely related. The two elements between ethics and ASN behavior support each other and have consequences, both administrative and legal sanctions if violated. This research is a normative legal research that uses secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. From the results of the study, it is known that the ethics and behavior of ASN have been regulated in Law Number 5 of 2014 concerning State Civil Apparatus jo. Government Regulation Number 53 of 2010 concerning Civil Servant Discipline, and Government Regulation Number 11 of 2017 concerning Management of Civil Servants. The application of ASN disciplinary sanctions is not only in the form of administrative sanctions in the form of a maximum dismissal, but also does not rule out the possibility of legal proceedings related to the said discipline violations if there are elements of criminal, civil and other legal aspects